SERANGAN, KEPADATAN POPULASI, DAN KEANEKARAGAMAN SERANGGA PADA PERTANAMAN JAGUNG YANG DIKELOLA DENGAN OLAH TANAH KONSERVASI VERSUS OLAH TANAH KONVENSIONAL DI NATAR, LAMPUNG SELATAN - F.X. Susilo dan I Gede Swibawa . (Universitas Lampung, 2001)
Infestation, population, and diversity of insects in corn fields managed under conservation versus full tillage in Natar, South Lampung. This experimental study that has been conducted during the rainy season of 2000 was aimed to document the attacks, population density and diversity of selected insects in corn fields managed under conservation tillage (sprayed with Roundup herbicide) versus full tillage systems (plowed, no herbicide). Three corn cultivars were planted in four 80 x 60 m plots (larger plots) differing in tillage systems (C7-CT= cultivar C7 grown under conservation tillage system; RRCorn-CT = RRCorn under conservation tillage; C7-FT = C7 under full tillage; Bisma-FT = Bisma under full tillage). All corn seeds were treated with imidacloprid insecticide except those sowed in a control plot (10 x 10 m) that was set up inside the larger plot. Variables being observed were (1) attacks of corn whorl maggots or other organisms, (2) attacks of leaf feeders and cornearworms and (3) diversity of surface active insects and population density of ants + mites. Results show that, first, seed treatment using imidacloprid insecticide could reduce corn whorl maggot attacks only in Bisma-FT. Second, leaf feeder attacks were varied across tillage systems but did not exceed 4% level. Meanwhile, despite apparently high attack of the cornearworm in the field, no significant injury was detected either in the harvested ears or seeds. Third, pitfalls caught at least 66 families of surface-active insects consisting mostly of ants (65%), springtails (12%), mites (8%) and spiders (5%). Tillage systems did not seem to affect the diversity of the surface-active insects. Compared with the other three plots, the RRCorn-CT plot was dwelled by more ants and mites. Ants and mites were both accounted for more seedling failure in the RRCorn-CT plot while corn whorl maggots were responsible for the seedling failure in the Bisma-FT plot.